Lymphatic filariasis related perceptions and practices on the coast of Ghana: Implications for prevention and control. - Ahorlu, C.K.; Dunyo, S.K.; Koram, K.A.; Nkrumah, F.K.; Aagaard-Hansen, J.; Simonsen, P.E. (Acta Tropica, 1999)
A qualitative study to investigate lymphatic filariasis related perceptions and practices that may be relevant for the design of appropriate health education and control programmes was conducted in four endemic villages in coastal Ghana. The villagers were aware of the common manifestations of filariasis, such as adenolymphangitis (ADL), lymphoedema, elephantiasis and hydrocele, which were specifically described with local terminology. ADL attacks were identified as the most dreaded health problem in the communities, and elephantiasis and hydrocele also ranked high in importance among reported diseases. Generally the respondents did not accept the mosquito theory of transmission, but they believed in other physical, and in spiritual and hereditary causes. Hydrocele was considered to have no link to the other disease manifestations. The manifestations were most often treated with herbal preparations which were used orally, smeared on affected parts or given as enema. In some cases the affected parts were scarified before herbal preparations were applied. The manifestations affected the work output of its victims and subjected them to hardships such as teasing, unsuitability for marriage, sexual dysfunction and divorce. Although the etiology was seen as different, the local perception of the developmental process of elephantiasis closely paralleled that of the biomedical understanding. It is suggested that this coincidence is used as an entry point for health education, to advance a broader biomedical knowledge on etiology, transmission and treatment options, and thereby to ensure co-operation of the target populations in the control of this complex disease.
Keywords: Lymphatic filariasis; Perceptions; Practices; Socio-economic consequences; Health education; Public health; Control; Ghana